Pengaruh Kemajuan Teknologi Terhadap Perilaku Sosial Siswa Sekolah Dasar - Ridla ‘Adawiyyah; Denis Desfriyati (Politeknik Kampar, 2024)
Technological developments are inevitable, we must be able to balance and keep up with the times. The presence of technology has influenced existing values. The changes that occur in society are increasingly evident, especially in lifestyles and lifestyles, attitudes that are increasingly selfish and pragmatic. In addition, technology in education is a system used to support learning activities to achieve the desired results. This research was conducted with the aim of knowing how the influence of technological advances on the social behavior of elementary school students, this research was also carried out with qualitative methods with literature studies or literature reviews. The technique used is data collection by searching for material related to what will be discussed digitally.